Analisis Komparatif Pendapatan Usaha Tani Cabai Antara Petani Swadaya Dengan Petani Penerima Pengembangan Kawasan Cabai Keriting Kecamatan Mendo Barat - Wikrawardana, Sucy; Agustina, Fournita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This study aims to compare the differences in farmers' income between independent curly chili farming and recipients of curly chili area development activities and to find out which curly chili farming is more profitable between independent smallholders and curly chili farmers from curly chili area development activities. The selection of the research location was done deliberately, the respondents were determined by using the Proportional Stratified Random Sampling technique. Respondents are farmers classified as independent smallholders and beneficiary farmers. There were 30 independent smallholder respondents and 30 beneficiary respondents. This study uses comparative analysis, income analysis and analysis of farm profits. The results of the study showed that the income of independent smallholders was Rp. 5,291,925,250,-/MT and beneficiary income of Rp. 5.305.861.283,-/MT. The results of the independent t-test obtained a t count of 2.42 > from a t table of 1.67 which means that the income of beneficiary farmers is higher than that of independent smallholders. The results of the analysis of farming profits show that beneficiary farming is more profitable, worth Rp. 9,565,000, - compared to independent smallholders.